The riddle of orange–red luminescence in Bismuth-doped silica glasses - Oleksii V. Laguta (Nature Portfolio, 2021)
Abstract For over the past two decades it has been believed that the intense orange-red photoluminescence in Bismuth-doped materials originates from Bi $$^{2+}$$ 2 + ions. Based on the results from magnetic circular polarization experiments, we demonstrate that this hypothesis fails for Bismuth-doped silica glasses. Our findings contradict the generally accepted statement that the orange-red luminescence arises from $$^{2}P_{3/2}(1)$$ 2 P 3 / 2 ( 1 ) $$→$$ → $$^{2}P_{1/2}$$ 2 P 1 / 2 transition in a divalent Bismuth ion. The degree of magnetic circular polarization of this luminescence exhibits non-monotonic temperature and field dependencies, as well as sign reversal. This complex behaviour cannot be explained under the assumption of a single Bi $$^{2+}$$ 2 + ion. The detailed analysis enables us to construct a consistent diagram of energy levels involved in the magneto-optical experiments and propose a new interpretation of the nature of orange-red luminescence in Bismuth-doped silica glass. A centre responsible for this notorious photoluminescence must be an even-electron system with an integer total spin, presumably a dimer of Bismuth ions or a complex consisting of Bi $$^{2+}$$ 2 + and an oxygen vacancy.